Micro-nano technology XVI : selected, peer reviewed papers from the 16th Annual Conference and 5th International Conference of the Chinese Society of Micro-Nano Technology (CSMNT 2014), August 31-September 3, 2014, Chengdu, China - Tang, Fei (Key engineering materials ;, 2015)
Collection of selected, peer reviewed papers from the 16th Annual Conference and 5th International Conference of the Chinese Society of Micro-Nano Technology (CSMNT 2014), August 31-September 3, 2014, Chengdu, China. The 226 papers are grouped as follows: Chapter 1: Materials and Technologies in the Scale of Micro and Nano; Chapter 2: Micro/Nanofluids Research and Technologies; Chapter 3: Measurements, Sensors and MEMS; Chapter 4: Micro Actuators and Devices; Chapter 5: Optics in the Scale of Micro and Nano; Chapter 6: Energy Harvesting, Power Supply and Technologies for Fuel Cells; Chapter 7.